Direct comparison of LES and experiment of a single-pulse impinging jet. (September 2015) - Bovo, M.; Davidson, L.
Highlights: Pulse impinging jet have remarkable heat transfer characteristics. Impinging jets are relevant to many technologies. Particularly relevant to internal combustion engines. Verification of LES ability to capture impinging jet heat transfer. Abstract: Experimental results are commonly used to validate numerical simulations. Often, it is challenging to accurately reproduce the experimental setups in the numerical environment, thereby leaving uncertainty in the validation process. An experiment on impinging jets was designed with boundary conditions well suited for implementation in the numerical environment. In this work, LES was implemented to specifically match the experiment of a single-pulse jet impinging on a surface oriented normally to the jet axis. The experiment was designed primarily to study the thermal effects on the impingement zone with high space–time resolution. The temperature evolution of the impingement target was measured via IR camera. The space–time resolved jet velocity-field was measured with PIV and was used as boundary condition for the simulation. The focus of the LES was to replicate the experiment as faithfully as possible in the virtual environment. LES was run multiple times to allow statistical evaluation of the results, as done in the experimental procedure. High levels of agreement were found between the LES and the experimental results, both from a qualitative and a quantitative point of view. This work could therefore be considered as a successful validation of the LES in the study of this type of flows.